POST-EVAR LIMB GRAFT KINKING — INTRA-OPERATIVE DIAGNOSIS - Coelho, Andreia (2020)
Introduction: Endograft limb kinking remains one of the major causes of secondary interventions and rehospitalisation after Endovascular aneurysm repair (EVAR). However, the importance of improving limb patency has received little focus. Endograft limb kinking also remains ill-defined, with considerable variability in the literature concerning its clinical presentation and natural history. The purpose of this paper is to search for an appropriate definition for limb graft kinking as well as intra-operative and follow-up approaches for a timely diagnosis. Methods: A literature review was performed in the MEDLINE database. Results: Several imaging methods have been reviewed, and they all present advantages and drawbacks. Completion Angiography (CA) is routinely performed after removal of stiff guidewires, but it is considered an inadequate means of determining high-risk limb grafts. Cone Beam Computed Tomography (CBCT) has been shown to be feasible both in EVAR planning and as completion imaging to detect complications missed by CA. Duplex Ultrasound, pressure measurement and intravascular ultrasound have also been proposed as adjuncts for intraoperative evaluation of limb grafts. Discussion: Standardizing criteria for hemodynamically significant kinking diagnosis is necessary in order to define patients that may benefit from re-interventions to reduce the risk of limb occlusion. Further studies are necessary in order to raise awareness for this complication which can lead to limb graft thrombosis and limb loss and in order to establish an appropriate diagnosis and follow up protocol.